Revision of Afrocrania (Coleoptera: Chrysomelidae, Galerucinae) Part I: Species in which the males have head cavities or extended elytral extrusions - Jens MIDDELHAUVE; Thomas WAGNER (European Journal of Entomology, 2001)
Material of Afrotropical Afrocrania Hincks, 1949 (= Pseudocrania Weise, 1892, not Pseudocrania M'Coy, 1851) is revised, and a redescription of the genus is given. This publication is on Afrocrania species in which males have head cavities or extended elytral extrusions. Species without those sexual dimorphic organs will be revised in a subsequent paper. Material of Pseudocrania latifrons Weise, 1892, Pseudocrania foveolata (Karsch, 1882) (= Monolepta africana Jacoby, 1894, = Pseudocrania nigricornis Weise, 1895), and Pseudocrania assimilis Weise, 1903 was examined; Pseudocrania basalis Jacoby, 1907 is excluded from Afrocrania; Afrocrania kaethae sp. n., A. luciae sp. n., A. kakamegaensis sp. n., A. longicornis sp. n., and A. ubatubae sp. n. are newly described species.